2021
DOI: 10.3389/fcell.2021.710721
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Photodynamic Therapy on Gemcitabine-Resistant Cholangiocarcinoma in vitro and in vivo Through KLF10 and EGFR

Abstract: Cholangiocarcinoma is a relatively rare neoplasm with increasing incidence. Although chemotherapeutic agent such as gemcitabine has long been used as standard treatment for cholangiocarcinoma, the interindividual variability in target and drug sensitivity and specificity may lead to therapeutic resistance. In the present study, we found that photodynamic therapy (PDT) treatment inhibited gemcitabine-resistant cholangiocarcinoma cells via repressing cell viability, enhancing cell apoptosis, and eliciting G1 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Radiation-induced KLF10 upregulation was noted in many cancer cell lines and murine models [83][84][85]. KLF10 transcriptionally downregulated EGFR and modulated gemcitabine-resistance in cholangiocarcinoma [86]. In esophageal squamous cell carcinoma, exosomes secreted from hypoxic tumors after radiation expressed high levels of miR-340-5p, which suppressed KLF10 transcription.…”
Section: Role Of Klf10 In Pdac Resistance To Radiotherapymentioning
confidence: 99%
“…Radiation-induced KLF10 upregulation was noted in many cancer cell lines and murine models [83][84][85]. KLF10 transcriptionally downregulated EGFR and modulated gemcitabine-resistance in cholangiocarcinoma [86]. In esophageal squamous cell carcinoma, exosomes secreted from hypoxic tumors after radiation expressed high levels of miR-340-5p, which suppressed KLF10 transcription.…”
Section: Role Of Klf10 In Pdac Resistance To Radiotherapymentioning
confidence: 99%
“…Furthermore, in vitro experiments of Gemcitabine and PDT showed that cholangiocarcinoma induces repressing cell viability, apoptosis, and eliciting of CCA in G1 phase via modulating cyclin D1 and caspase 3 cleavage. and prevents tumor growth in vivo ( 147 ). In addition, Mascaraque and colleagues evaluated the PS ability of metformin (Metf) on BCC cells.…”
Section: Cca Following Pdtmentioning
confidence: 99%
“…PDT has been listed in the guidelines of the National Comprehensive Cancer Network (NCCN) of CCA (Benson et al, 2014). It has been found that PDT can kill cholangiocarcinoma cells by inhibiting cell cycle and promoting apoptosis (Yang et al, 2021). Simultaneously, multi-kinase inhibitors targeting Ras, Raf, vascular endothelial growth factor and fibroblast growth factor receptor can also generate ROS and have certain anti-CCA effects, improving the prognosis of metastatic/unresectable patients (Xie et al, 2016;Cousin et al, 2022).…”
Section: Introductionmentioning
confidence: 99%